2014
DOI: 10.1083/jcb.201408002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of IFT70/52 and IFT52/46 provide insight into intraflagellar transport B core complex assembly

Abstract: Crystallographic analysis of the B core complex of the intraflagellar transport machinery provides insight into the molecular basis of ciliogenesis defects caused by several specific IFT mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
240
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(263 citation statements)
references
References 52 publications
21
240
2
Order By: Relevance
“…These two IFT‐B1 (core) and IFT‐B2 (“peripheral”) subcomplexes can be purified independently using recombinant proteins (Fig 1 and Taschner et al , 2014) and when incubated result in the reconstitution of a nearly complete 15‐subunit IFT‐B complex lacking only IFT56 (Fig 7A). We uncovered that the IFT57/38 subcomplex is central to IFT‐B complex assembly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These two IFT‐B1 (core) and IFT‐B2 (“peripheral”) subcomplexes can be purified independently using recombinant proteins (Fig 1 and Taschner et al , 2014) and when incubated result in the reconstitution of a nearly complete 15‐subunit IFT‐B complex lacking only IFT56 (Fig 7A). We uncovered that the IFT57/38 subcomplex is central to IFT‐B complex assembly.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested an interaction of mouse TTC26 with IFT46 based on yeast‐2‐hybrid analysis and pull‐downs (Swiderski et al , 2014), making it the tenth member of the IFT‐B1 complex. Although we currently have a good biochemical understanding of how the 15‐subunit IFT‐B complex assembles and have crystal structures of domains and heterodimeric subcomplexes (Figs 3 and 6; Taschner et al , 2014; Bhogaraju et al , 2011), information on how IFT proteins organize the IFT complex in 3‐dimensions is still missing. The reconstitution of the 15‐subunit IFT‐B complex (Fig 7) will pave the way for structural studies of this assembly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations